Maths made easy. key stage 2, ages 10-11 workbook 2 - Kennedy, John; McArdle, Sean Vorderman, Carol (Dorling Kindersley London, 1999)
One of a scheme of home-study workbooks designed to reinforce all aspects of children's school work. The exercises have been written in line with the National Curriculum requirements for maths, incorporating the latest developments in the implementation of the National Numeracy Strategy.